2011
DOI: 10.1590/s0034-737x2011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Associação de Rhizobium sp. a duas leguminosas na tolerância à atrazina

Abstract: Association of Rhizobium sp. with two legumes on atrazine toleranceThe association of bacteria with plants has been studied as a possible emerging technology for phytoremediation of contaminants, including herbicides, which pose as a threatening to environmental quality due to their recalcitrance. The aim of this study was to assess the tolerance of dwarf mucuna (Stizolobium deeringianum Bort) and black mucuna (Stizolobium aterrimum Piper & Tracy) inoculated and uninoculated with Rhizobium to the herbicide atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
0
1
1
Order By: Relevance
“…Because atrazine has mobility in the soil, these symptoms were found in some plants for all depths evaluated. These results are different from those observed by Camargo et al (2011), who found severe intoxication symptoms, as the dose of the herbicide atrazine was increased using a red latosol with a clay texture.…”
Section: Resultscontrasting
confidence: 99%
“…Because atrazine has mobility in the soil, these symptoms were found in some plants for all depths evaluated. These results are different from those observed by Camargo et al (2011), who found severe intoxication symptoms, as the dose of the herbicide atrazine was increased using a red latosol with a clay texture.…”
Section: Resultscontrasting
confidence: 99%
“…BRS Piatã e U. ruziziensis, quando semeadas na densidade de 10 kg ha -1 , aos 24 dias após a emergência da soja, reduziram a produtividade desta cultura de forma distinta, com decréscimos de 3,03 e 16,23%, respectivamente (Saraiva et al, 2013). Diversos autores relatam U. brizantha e B. pilosa como plantas daninhas de grande importância para diversas culturas (Biffe et al, 2010;Pinotti et al, 2010;Camargo et al, 2011;Pereira et al, 2012), inclusive para soja (Oliveira et al, 2013).…”
Section: Introductionunclassified